Role of Surface Modification in Synthesis of Structurally Well-Defined Silica Nanoparticles for Oil and Gas Applications - Zaid, H.M. (Springer Science and Business Media B.V., 2021)
Silica nanoparticles, as an improved oil recovery agent, have shown the ability to stimulate oil mobility. However, typical oil reservoir conditions with high temperature, salinity and pH modifies the way that nanoparticles interact with the porous medium, by causing the agglomeration leading to the particlesâ retention. Spherical, monodisperse silica nanoparticles (SiO2 NPs) were synthesized via a one-step solâgel method assisted by in-situ surface modification and characterized using various techniques. In this work, Triton X-100, as a surface-modification agent, was added during the hydrolysis of tetraethoxysilane (TEOS) in methanol to study their effect on morphology and size of the nanoparticles under varying ratio. The particle shape and size was determined using a field-emission scanning electron microscopy (FESEM), exhibiting the well-defined spherical particles with particle diameter between 13 and 27Â nm. The obtained results also showed that an increase in the ratio of methanol to the surfactant Methanol/Triton TX-100 produces a decrease in particle size. Furthermore, an energy dispersive x-ray spectroscopy (EDX) pattern was used to analyse the compositional ratio of silicon and oxygen to verify the surface-modification of SiO2 nanoparticles. By X-ray diffraction (XRD), a broad peak of pure amorphous nature of SiO2 is observed. While, the chemical binding of Triton X-100 on to the SiO2 nanoparticles was studied by infrared spectroscopy (FTIR). Lastly, surface area of nanoparticles showed an increment as the molar ratio Methanol/Triton TX-100 increased. All these results indicate that the surface modification plays an important role in effectively control the size and morphology of the SiO2 nanoparticles, without the presence of agglomerations. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.